The effectiveness of state intervention in the South African electronics industry - Aspin, Robert Melvin (School of Economics, 2023)
The objective of this dissertation is to assess the effectiveness of state intervention in the South African electronics industry. In order to assess the impact of the various policies implemented by the government, a nation wide survey, which encompassed 270 firms in the industry, was undertaken. The data collected suggests that the state has been unsuccessful in its attempt to develop the industry. It was confirmed that, in comparison with many other developing countries, its growth has been slow and that it continues to rely heavily on imports and foreign technology. One of the reasons for this lack of success is argued to be the lack of any meaningful interaction between government and the industry. Based on the findings of the survey, the major recommendation to emerge is that the government should, in consultation, modify specific policies to promote the establishment of a dynamic, resilient and internationally competitive industry. Chapter One outlines the important role played by the electronics industry in the process of economic development. The industry is depicted as being central to the process of industrialisation in South Africa and its positive effect on productivity in other sectors is stressed. Chapter Two outlines two forms of interventionist policy with which the state can influence the industry's development. Both trade and technology policy, by providing the structures with which to protect and subsidise the industry, play a decisive role in the development of a technology intensive industry. Chapter Three deals with the methodology of the nationwide survey of the electronics industry in South Africa. In Chapter four the industry's development is assessed and various data pertaining to production and value added are evaluated. It is found that it relies heavily on imports and that production constitutes less than 30 percent of the sector's market value. Chapter Five provides an overview of current state policy with regard to the electronics industry. It is noted that the state has used various measures to· stimulate its growth, including providing tariff protection from imports, tax deductible allowances, long-term loans, and grants. Furthermore, a number of groups and committees whose task it is to monitor and make recommendations affecting the industry, have been established. The various reasons for the industry's limited development are examined in Chapter Six. This analysis draws largely on empirical data obtained in the survey and focuses on the effectiveness of various state policies. The survey highlighted that skilled labour shortages, high cost structures, technological dependence, and the lack of exports, all account for the slow growth of the industry. chapter. seven examines policy alternatives for the further development of the local industry. These include proposals from the state sector, those made by respondents in the survey and those gleaned from international experience. Final recommendations and conclusions, reached in the course of the dissertation, are made in Chapter Eight.